Strengthening The Legal Basis As A Way Of Growing A Sense Of Nationalism - Ardika, Nyoman; Muhamad Soleh (CV. Inara, 2022)
Nationalism is a form of national awareness of the nation and state itself. The fading sense of nationalism can threaten and destroy the country from within. This happens because national resilience will be weak and easily penetrated by outsiders. This requires the role of law as the basis that regulates the existence of nationalism so that it can live and be lived by the community. Especially in this modern era, it is undeniable that the spirit of nationalism has faded, and the law is ignored. This research is a type of descriptive research through a qualitative approach. The strategy used is a case study, data collection techniques with observation, interviews, and documentation. Data analysis using interactive analysis techniques. Based on the results of the research that has been done, it can be seen that the growth of solid nationalism is very much needed for the people of a nation who want to continue to exist, treading the life journey of the country and state with their ideals and goals. . Especially in this modern era, it is undeniable that the spirit of nationalism has faded and has an impact on decreasing legal awareness.